Physics experimentation skills grade 9 & 10 supplementary reading material - Khan ullah aamir (Islamabad National book foundation, 2025)
This supplementary material is designed to strengthen students' practical skills in physics experiments for Grades 9 and 10. It guides students on how to set up experiments, use laboratory equipment like stopwatches, meters, and electric circuits, and collect accurate data. The material emphasizes the scientific method, including observation, measurement, analysis, and drawing conclusions. Key experiments cover topics like forces, energy, waves, electricity, and heat, aiming to connect theoretical concepts with hands-on experience and critical thinking.